DNA methylation of ANKRD23 as a novel biomarker for early diagnosis of ovarian cancer - Aydan Alizada; Ozge S. Erdogan; Seda K. Erciyas; Betul C. Demirbas; Ozge Pasin; Ahmet Dinc; Pınar Saip; Hulya Yazici; Seref B. Tuncer (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
Ovarian cancer (OC) is a leading cause of gynecologic cancer-related mortality and is frequently diagnosed at advanced stages due to the absence of effective early detection tools. Epigenetic alterations, particularly DNA methylation, play a critical role in tumorigenesis and represent promising non-invasive biomarkers. This study investigated the methylation status of the ANKRD23 gene in OC and evaluated its diagnostic potential using peripheral blood samples. A total of 385 serous OC patients, 50 individuals with benign ovarian conditions, and 99 healthy controls were included. DNA methylation was assessed using methylation-sensitive restriction enzymes followed by real-time PCR. ANKRD23 methylation was significantly associated with clinical stage (p = 0.029), histological grade (p = 0.009), and ethnicity (p = 0.024). Moreover, methylation levels differed significantly among OC patients, benign cases, and healthy controls (p = 0.026). These findings support blood-based ANKRD23 methylation as a promising biomarker for non-invasive ovarian cancer diagnosis and risk stratification.